“Symphonia”? A New Patriarch Attempts to Redefine Church–State Relations in Serbia - Aleksov Bojan; Lackenby Nicholas (Comparative Southeast European Studies, 2023)
The authors examine the relationship between Church and state in Serbia since the election of the new patriarch in February 2021. They demonstrate the ways in which Church and state have begun to take divergent paths. This is not to suggest that political and ecclesiastical power are not deeply entwined in contemporary Serbia—they are. However, the authors show how—contrary to accounts which present Church and state as practically homologous—clerical and political leaders are increasingly pulling in different directions. They evaluate the key features of what has so far been a brief, but momentous tenure of the Serbian Patriarch Porfirije. A particular emphasis is placed on the new patriarch’s ecclesiastical diplomacy, the ever-increasing role of the Church as a mnemonic agent, the Church’s reaction to Belgrade hosting an LGBT pride parade and, finally, its rapport with the Serbian government.